2021
DOI: 10.1108/jpbm-12-2020-3281
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on online product reviews

Abstract: Purpose The ongoing COVID-19 pandemic has led to drastic changes in the lives of customers. Social isolation, financial difficulties, fear of being infected and many other factors have caused the psychological well-being of customers to deteriorate. By taking up the role of online reviews in the regulation of consumers’ moods, this study aims to examine the changes that have occurred in online product ratings, as well as the negative tone and word counts of product reviews during the COVID-19 pandemic. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…The value placed on features such as safety, social distancing and mask policies are considered as important as previously dominant features such as service, overall experience and food quality [ 16 ]. Kutlubay et al [ 105 ] examined the differences in comments and ratings provided by customers before and after the COVID-19 outbreak. They showed that the customer ratings had dropped during the pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…The value placed on features such as safety, social distancing and mask policies are considered as important as previously dominant features such as service, overall experience and food quality [ 16 ]. Kutlubay et al [ 105 ] examined the differences in comments and ratings provided by customers before and after the COVID-19 outbreak. They showed that the customer ratings had dropped during the pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…1,3,4 This affects individual and social behaviors widely, notably in the fields of public health, 4,5 social contact, 6 and marketing. [7][8][9][10] Complaining is the concrete reflection of human negative psychological factors. 11 CCB is bound to be influenced by negative psychological effects on consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the entire country was forced into a lockdown. Therefore, referring to Kutlubay et al (2021), the observation period was shortened from July 2019 to January 23, 2020, using the lockdown date as the criterion. Thus, we excluded the possibility that the epidemic may have an impact on our conclusion through the alternative regression.…”
Section: Resultsmentioning
confidence: 99%